Speed studies in Singapore - Teo, Boon Fang (2018)
In a country with a dense road network system like Singapore, appropriate speeds and speed limits are issues that authorities must deal with when a new road is built, or when an existing road needs to be reviewed. As the road network expands, and as we review roads at increasing frequency with constantly changing demographics, there is a need to deepen our understanding on the factors affecting decisions surrounding speed limits, and how our vehicles speeds impact road safety. Speed limit can be controlled by using both physical and non-physical vehicle speed reduction measures. Physical measures are measures that affect the vehicle or the driver physically, and they include but are not limited to: humps, speed regulating strips, and chicanes. Non-physical measures are measures that fall outside the category of physical measures, and they include but are not limited to: speed cameras, traffic calming markings, and speed limit signs. This project will address the effectiveness of various speed reduction method, and the study is conducted to help readers better understand the different vehicle speed reduction measures currently in place at selected locations. Through statistical analysis, my partner Luan Yuanfeng and I investigate the effectiveness of these various measures, with mine being to focus on physical speed reduction measures. The data analysis shows that physical speed reduction measures in decreasing order of effectiveness are silver zones, humps (normal), raised pedestrian crossing, speed regulating strips. Referencing to Yuanfeng’s work on the effectiveness of non-physical speed reduction measures, we would recommend physical and non-physical speed reduction measures be used in conjunction.